2015
DOI: 10.3892/mmr.2015.3498
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-509-3p inhibits cancer cell proliferation and migration by targeting the mitogen-activated protein kinase kinase kinase 8 oncogene in renal cell carcinoma

Abstract: Abstract. microRNAs (miRNAs; miR) are a class of small non-coding RNA molecules, which are involved in the pathogenesis of human diseases through the negative regulation of gene expression. Previous studies have demonstrated that miR-509-3p is a novel miRNA associated with cell proliferation and migration in 786-O renal cell carcinoma (RCC) cells. However, the mechanism of action of miR-509-3p in RCC remains to be elucidated. The present study aimed to examine the functional role and mechanism of miR-509-3p in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 23 publications
4
28
0
Order By: Relevance
“…Additionally, functional analyses demonstrated that hsa-mir-509–3p binds and negatively regulates the transcription of CD44 more strongly in C allele carriers than in T allele carriers13151617. These results support previous studies that have implicated hsa-mir-509–3p as a tumor suppressor gene in the development of human cancer293031.…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, functional analyses demonstrated that hsa-mir-509–3p binds and negatively regulates the transcription of CD44 more strongly in C allele carriers than in T allele carriers13151617. These results support previous studies that have implicated hsa-mir-509–3p as a tumor suppressor gene in the development of human cancer293031.…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have revealed that miRNAs have unique expression profiles in different types of cancer or diseases at different stages, which indicates that miRNAs could be used as biomarkers for diagnosis and serve a significant role in the occurrence and development of tumors (21,22). In RCC, certain miRNAs have been described as either oncogenes or tumor suppressors based on the function and expression level of miRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…miR-509-3p, a significant regulator of the MAP3K8 oncogene was shown to be down regulated in tumor cells [71]. Furthermore, downregulation of miR-509-3p was shown to be a tumor suppressor in tumor cells and associated with tumor cell invasion and migration [72].…”
Section: Discussionmentioning
confidence: 99%